Erbium Laser Therapy for Treating Onychomycosis - Huacuja, Aristides Arellano (An Overview of Disease and Health Research Vol. 2, 2025)
Onychomycosis is the disease that can most frequently affect the nails of humans (50%), being responsible for more than half of the cases of nail infection. Fungal nail infections are caused by various fungal organisms (fungi). This case aimed to explore Erbium Laser Therapy for treating Onychomycosis. Often, the cause of the disease is a type of fungus called “dermatophyte”. Yeasts and moulds can also cause infections. The infections can occur at any age, but are more common in older people. As the nail ages, it can become brittle and dry out. The cracks, porosity that are present in the nails are the reason for allowing the entry of fungi. Other factors, such as decreased blood circulation to the feet, which occurs because diabetes is present and a weakened immune system, can also play a role. An inflammatory infection of the toenails can start changing the nail colour in athlete's foot (foot fungus) and can extend from one nail to another. However, getting an infection from another person can occur if they employ the same nail cutter. There is a traumatic factor also due to an accident or shoes to tight. The treatment of onychomycosis may require taking oral antifungal medications combined with long-term treatment. In addition, other treatments can be performed, ranging from surgery (laminectomy, matrixectomy), onychomycosis, to the use of new therapies such as photodynamic therapy, iontophoresis, and lasers today. Erbium lasers have been a very successful treatment in our patients with these diseases. it applied weekly in all the nails, infected or not?